Linguistic Means of Image Development of Gerhard Chroeder in the Run up to and After First Year in Office - E. S. Goncharova (Vestnik MGIMO-Universiteta, 2015)
This article is dedicated to the analysis of the linguistic means that influenced image development of the German Chancellor Gerhard Schroeder in the run-up and during the first year in office. Based on printed Media materials, this survey educed the linkage between the evolution of journalists' assessments of personality and activities of G. Schroeder and his public support at the elections in 1998 and parliamentary elections in 1999. The analysis of the articles about the Chancellor showed a great number linguistic means that were used to describe him and that contributed to his image development. Linguistic means with positive connotation were primarily used to describe G. Schroeder in the run-up, since he was reliant on. In contrast, the journalists became more skeptical about the Chancellor after his first year in office and started to describe him with linguistic means with negative connotation. Metaphor is the most widely used linguistic means before and after elections. Beside it, the journalists often used antonomasia, epithets, and similes to form the positive image of the politician. The use of antithesis was connected with the desire to put up Schroeder in a positive light against his predecessor. With growing disappointment with the Chancellor many metaphors and epithets receive their antonymous meaning. The survey results are presented in the table.